2022
DOI: 10.18047/poljo.28.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Komparativni učinak različitih insekticida i kaolina na smanjenu brojnost populacije Cacopsylla pyri L.

Abstract: Cacopsylla pyri L. (Hemiptera: Psyllidae) is one of the most serious economic pear pests in Eastern Croatia. Previous methods of pear control in the Republic of Croatia have led to the development of an insect population resistant to certain active ingredients. The objectives of this two-year study were to determine the optimal number of treatments for psylla control based on the monitoring of pest life cycle and to determine the effectiveness of processed kaolin in controlling the pear psylla in comparison wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…The effectiveness of the treatment depended greatly on weather conditions and ranged from 37% in 2018 to 71% in 2017. In 2017, when the high effectiveness of kaolin clay was achieved, the results were very similar to those of chemical insecticides in terms of the number of eggs and different stages of larvae, while in 2018, these values were statistically significantly lower for kaolin clay [13]. This research concluded that kaolin clay should not be used alone, but its application within an integrated pest management practice yields very good results.…”
Section: Kaolin As a Non-chemical Alternative In Controlling C Pyrimentioning
confidence: 55%
See 2 more Smart Citations
“…The effectiveness of the treatment depended greatly on weather conditions and ranged from 37% in 2018 to 71% in 2017. In 2017, when the high effectiveness of kaolin clay was achieved, the results were very similar to those of chemical insecticides in terms of the number of eggs and different stages of larvae, while in 2018, these values were statistically significantly lower for kaolin clay [13]. This research concluded that kaolin clay should not be used alone, but its application within an integrated pest management practice yields very good results.…”
Section: Kaolin As a Non-chemical Alternative In Controlling C Pyrimentioning
confidence: 55%
“…In specific research, this true bug was present when organophosphorus insecticides were excluded from the treatment programme, while it was not found in the year when this group of insecticides was used. The use of kaolin-based preparations as a repellent for the pear psylla is effective and safer for natural enemies [13,47].…”
Section: Specialist Predatorsmentioning
confidence: 99%
See 1 more Smart Citation